Perbedaan Lama Perendaman Sari Belimbing Wuluh terhadap pH, Kadar Air, dan Daya Ikat Air Daging Dada Itik Magelang - Hidayah, Nur; Pramesty, Dedika Nanda; Idayanti, Rahma Wulan (Journal Galung Tropika, 2024)
Duck is one type of waterfowl that has a higher nutritional content than chicken. The high nutritional value causes the duck meat to be easily damaged perishable food due to the high water content, the pH value is close to neutral and sufficient food is available for microbes. An alternative effort is needed for natural ingredients that are safe but can inhibit microbial growth in duck meat. One of the natural ingredients that can be used is star fruit (Averrhoa bilimbi L.) because it has a high acid content. This study aims to determine the difference in the duration of soaking Magelang duck meat with starfruit juice on the pH value, water holding capacity and water content. The research method was carried out using a completely randomized experimental design (CRD) with 4 treatments and 5 replications, and using a 40% concentration of starfruit juice with a soaking time of 0, 20, 40, 60 minutes. The data obtained were analyzed by analysis of variance and if different results were obtained, it was continued with the Duncan Multiple Rang Test (DMRT) further test. The results showed that the immersion time for 20-60 minutes can lower the pH value (5,83-4,67) and water content (67,05-63,68%), but had no effect on water holding capacity (48,47-54,63%). It is concluded that the immersion time of 60 minutes with starfruit juice with a concentration of 40% in can be used as a method of preserving Magelang duck breast meat.